Metal Nanocluster—Metal Organic Framework—Polymer Hybrid Nanomaterials for Improved Hydrogen Detection - Richard Palmer (Small, 2022)
The development of hydrogen sensors is of paramount importance for timely leak detection and remains a crucial unmet need. Palladium-based materials, well known as hydrogen sensors, still suffer from poisoning and deactivation. Here, a hybrid hydrogen sensor consisting of a Pd nanocluster (NC) film, a metal–organic framework (MOF), and a polymer, are proposed. The polymer coating, as a protection layer, endows the sensor with excel-lent H2 selectivity and CO-poisoning resistance. The MOF serves as an interface layer between the Pd NC film and the polymer layer, which alters the nature of the interaction with hydrogen and leads to significant sensing performance improvements, owing to the interfacial electronic coupling between Pd NCs and the MOF. The strategy overcomes the shortcomings of retarded response speed and degraded sensitivity induced by the polymer coating of a Pd NC film–polymer hybrid system. This is the first exhibition of a hydrogen-sensing enhancement mechanism achieved by engineering the electronic coupling between Pd and a MOF. The work establishes a deep understanding of the hydrogen-sensing enhancement mechanism at the nanoscale and provides a feasible strategy to engineer next-generation gas-sensing nanodevices with superior sensing figures of merit via hybrid material systems.